The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/3742684
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Appearance of Oropharyngeal and Upper GI Kaposi’s Sarcoma in an Immunocompromised Patient

Abstract: Introduction. Kaposi's sarcoma (KS) usually manifests as a cutaneous disease but GI manifestation is often rare. It is associated with human herpes virus-8 (HHV-8) and seen in immunocompromised patients. In the USA, use of highly active antiretroviral therapy (HAART) has drastically reduced incidence of KS in HIV patients. Case Presentation. A 65-year-old male with human immunodeficiency virus (HIV) was admitted to the intensive care unit (ICU) with cardiopulmonary arrest secondary to hyperkalemia of 7.5 meq/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the last 10 years, only 3 case reports have described patients with gastrointestinal lesions in the absence of cutaneous manifestations, as in our patient [ 6 , 9 , 10 ]. One case report by Daar et al in 2017 showed a similar presentation in a 65-year-old man with upper gastrointestinal lesions in the absence of cutaneous lesions, following a sharp drop in the hemoglobin level and findings of stool occult blood on admission.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the last 10 years, only 3 case reports have described patients with gastrointestinal lesions in the absence of cutaneous manifestations, as in our patient [ 6 , 9 , 10 ]. One case report by Daar et al in 2017 showed a similar presentation in a 65-year-old man with upper gastrointestinal lesions in the absence of cutaneous lesions, following a sharp drop in the hemoglobin level and findings of stool occult blood on admission.…”
Section: Discussionmentioning
confidence: 68%
“…AIDS-Kaposi sarcoma presenting exclusively with gastrointestinal lesions is seldom described in the literature. It is reported that 90% of Kaposi sarcoma presentations involve cutaneous lesions [ 6 ], with dark, violaceous plaques and nodules on the epidermis and mucosa. Few case reports have shown Kaposi sarcoma lesions in the setting of gastrointestinal bleeding; however, in most of these case reports, gastrointestinal lesions were also accompanied by dark violaceous cutaneous lesions on the face, trunk, or extremities [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaposi's sarcoma is rarely found in the esophagus, and presents as dysphagia rather than odynophagia [ 5 ]. It appears as submucosal ulcerations or as linitis plastica in the stomach [ 6 ]. While Kaposi’s sarcoma lesions in the latter parts of the upper GI tract are generally asymptomatic, it has been reported to cause acute hemorrhage [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears as submucosal ulcerations or as linitis plastica in the stomach [ 6 ]. While Kaposi’s sarcoma lesions in the latter parts of the upper GI tract are generally asymptomatic, it has been reported to cause acute hemorrhage [ 6 , 7 ]. Our study did not document any cases of CMV/HSV infection or cases of Kaposi’s sarcoma or lymphoma, likely due to a relatively small sample size and higher CD4 count than that is usually found in patients with these disease entities.…”
Section: Discussionmentioning
confidence: 99%